PERSEPSI ETNIS CHINA TERHADAP PERBANKAN SYARIAH DI KOTA MEDAN - Harviz Akbar; Haroni Doli Hamoraon Ritonga (Departemen Ekonomi Pembangunan USU, 2013)
The growth of syariah bank assets is better than the growth of conventional bank. The growth of syariah bank assets reaches double digits even rerely below 30% in the last 10 years. Even the growth of the total asset of has been able to compete with the level of assets of Islamic bank of Malaysia. This research only focused on China ethnic live in the city of Medan. The aim of this research is to observe what the impact of work, service, promotion and physical evidence of the China ethnic perception on syariah bank of Medan. The respondents of this research are university student, employees, industrialist entreprenuer and other self-employed works. The writer uses primary data obtained from interview, observation and questionnaire. For sample 60 respondent by using non probability methonds of sampling. To procees the data, the writer use Ordinary Least Square.The result of this research is a positive relationship of variables of work, service, promotion and physical evidence on syariah banking in Medan. Keywords: Shariah Banking, Conventional Banking, China Ethnic